PREVALENSI DEMAM BERDARAH DENGUE (DBD) PRIMER DAN SEKUNDER BERDASARKAN HASIL PEMERIKSAAN SEROLOGIS DI RUMAH SAKIT BALIMED DENPASAR - Citta Saraswati, Luh Putu; Mulyantari, Ni Kadek (E-Jurnal Medika Udayana; Vol 6 No 8 (2017): E-Jurnal Medika Udayana, 2017)
Dengue infection is one of antrhopoda-virus infection  caused by dengue virus with broad clinical spectrum. Primary infection caused by one serotipe virus manifest as dengue fever virus or dengue hemorrhagic fever. But, if infected with different serotipe virus, the manifestation will be more severe and increases the risk of dengue hemorrhagic fever and dengue shock syndrome. This condition affirm the importance of clinical laboratory examination especially serology examination that could be used to distinguish between primary dengue infection or secondary dengue infection more quickly. A cross sectional study was done at Balimed Hospital Denpasar in Januari-June 2014. The diagnosis following WHO criteria and immunocromatographic test (ICT) for Anti dengue IgM-IgG have been conducted. The data were grouped by aged and gender. Among 454 clinically suspected cases analysed, 366 (80,61%) cases were seropositive for dengue infection. Among the seropositive,  61 (13,43%) were positive for Anti dengue IgM and 238 (52,42%) were positive for Anti dengue IgG. Both Anti dengue IgM & IgG were positive in 67 (14,75%). Based on gender, the results show primary dengue infection in male 13,16 % and female 12,79 %.While secondary dengue infection in male 68,72 % and female 65,40 %. Based on aged, most of primary dengue infection were the age group 6 -11 years (26,66%) and secondary dengue infection were the age group 26-45 years (82,17%). It can be concluded the prevalence of primary and secondary dengue infection is higher in male than female. Most of primary dengue infection are children and most of secondary dengue infection occurring in adult. The result of this research was expected can be used as the basis of further research to find the risk factors associated with dengue infection.   Keywords: primary dengue infection, secondary dengue infection, IgM, IgG